An exploration of potential output measures to assess efficiency and productivity for labour and birth in Australia - Bonnie Eklom; Sally Tracy; Emily Callander (BMC, 2021)
Abstract Background In maternity services, as in other areas of healthcare, increasing emphasis is placed on improving "efficiency" or "productivity". The first step in any efficiency and productivity analysis is the selection of relevant input and output measures. Within healthcare quantifying what is produced (outputs) can be difficult. The aim of this paper is to identify a potential output measure, that can be used in an assessment of the efficiency and productivity of labour and birth in-hospital care in Australia and to assess the extent to which it reflects the principles of woman-centred care. Methods This paper will survey available perinatal and maternal datasets in Australia to identify potential output measures; map identified output variables against the principles of woman-centred care outlined in Australia's national maternity strategy; and based on this, create a preliminary composite outcome measure for use in assessing the efficiency and productivity of Australian maternity services. Results There are significant gaps in Australia's maternity data collections with regard to measuring how well a maternity service is performing against the values of respect, choice and access; however safety is well measured. Our proposed composite measure identified that of the 63,215 births in Queensland in 2014, 67% met the criteria of quality outlined in our composite measure. Conclusions Adoption in Australia of the collection of woman-reported maternity outcomes would substantially strengthen Australia's national maternity data collections and provide a more holistic view of pregnancy and childbirth in Australia beyond traditional measure of maternal and neonate morbidity and mortality. Such measures to capture respect, choice and access could complement existing safety measures to inform the assessment of productivity and efficiency in maternity care.